EXPLORING THE ROLE OF ARTIFICIAL INTELLIGENCE IN SUPPLY CHAIN MANAGEMENT FOR SMES: CRITICAL SUCCESS FACTORS AND THE IMPACT OF ENVIRONMENTAL UNCERTAINTY (Journal of Informatics Education and Research, 2024)
This study looks at how Artificial Intelligence (AI) helps Small and Medium-sized Enterprises (SMEs) improve their supply chain management, with a focus on important factors that affect its use in uncertain environments. The main goals of this study are to identify key success factors for effective AI integration in supply chains and to examine how identified success factors interact with environmental uncertainties.Using a quantitative approach, the study measures how often SMEs adopt AI, checks their performance indicators, and analyzes how different external uncertainties impact supply chain efficiency. The results show that using AI well can greatly boost the operational efficiency and flexibility of SMEs. Key factors for success include strong leadership support, active employee participation, and a solid technological foundation. Importantly, the research finds that SMEs in unstable environments can better handle risks and quickly adjust to market changes with AI strategies. This is especially relevant for healthcare, where having a strong supply chain is vital for timely medical supply delivery and good patient care. By focusing on how AI use and environmental factors interact, this study provides important insights for healthcare providers looking to use technology to improve supply chain speed and responsiveness. Overall, this research adds to the ongoing discussion about digital change in supply chains, stressing the importance for SMEs to embrace AI technologies to succeed in a more uncertain business world.